Hair scare - Doyle, Malachy; Allen, Jonathan (Sea Girt, NJ : Dingles & Co., 2007)
After making a wish that he were grown up, Jamie develops a hairy problem.
"This Americanization of Hair scare originally published in English in 2005 is published by arrangement with Oxford University Press"--P. [4] of cover.
Keywords: Mustaches; Wishes